2006
DOI: 10.1111/j.1600-0722.2006.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

The amelogenin story: origin and evolution

Abstract: Genome sequencing and gene mapping have permitted the identification of HEVIN (SPARC-Like1) as the probable ancestor of the enamel matrix proteins (EMPs), amelogenin (AMEL), ameloblastin (AMBN) and enamelin (ENAM). We have undertaken a phylogenetic analysis to elucidate their relationships. AMEL genes available in databases, and new sequences obtained in blast searching genomes or expressed sequence tags, were compiled (22 full-length sequences), aligned, and the ancestral sequence calculated and used to searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 34 publications
1
40
1
Order By: Relevance
“…Based on the generally accepted molecular clock hypothesis, we previously estimated that SPARCL1 arose from SPARC not so long before the divergence of rayfinned fish and lobe-finned fish [Kawasaki et al, 2004]. In contrast, a different study estimated the divergence date between SPARC and SPARCL1 to be in the Precambrian [Delgado et al, 2001;Sire et al, 2006], which is significantly earlier than our estimate. However, neither of these two studies used SPARC genes of cartilaginous fish or jawless vertebrates.…”
Section: The Origin Of Sparcl1contrasting
confidence: 55%
See 1 more Smart Citation
“…Based on the generally accepted molecular clock hypothesis, we previously estimated that SPARCL1 arose from SPARC not so long before the divergence of rayfinned fish and lobe-finned fish [Kawasaki et al, 2004]. In contrast, a different study estimated the divergence date between SPARC and SPARCL1 to be in the Precambrian [Delgado et al, 2001;Sire et al, 2006], which is significantly earlier than our estimate. However, neither of these two studies used SPARC genes of cartilaginous fish or jawless vertebrates.…”
Section: The Origin Of Sparcl1contrasting
confidence: 55%
“…The substitution rates are extremely high in these salivary and casein genes [Sabatini et al, 1993]. In contrast, dentin/bone and enamel SCPP genes evolve more slowly; significant sequence homology is detectable among the orthologous dentin/bone and enamel genes of mammals, birds, and amphibians [Toyosawa et al, 1998;Shintani et al, 2003;Kawasaki and Weiss, 2006;Sire et al, 2006].…”
Section: Scpp Genes Of Placentals Marsupials and Monotremesmentioning
confidence: 99%
“…3 ) and from sequence analysis ( fig. 1 , 2 and Sire et al [2006]). Indeed, the roughly conserved features of the N-terminal region suggest not only a common origin but also some functional similarities (they are all ameloblast-expressed proteins).…”
Section: Relationships Of Ameloblast-expressed Scpp Genesmentioning
confidence: 99%
“…quences, sequences retrieved in the databases, and new sequences; see Sire et al [2006] for the species list). The sequences were aligned as described above for AMTN and ODAM, and a putative AMEL ancestral sequence was calculated using PAUP 4.0.…”
Section: The Evolutionary Origin Of Amelmentioning
confidence: 99%
“…However, the expression of mouse Am was evident in epithelium-derived tissues of 1-week recombinant explants. It was reported that homologs of the mammalian enamelin and amelogenin genes have not been detected in the chick genome, but that they have been detected in reptiles and amphibians (Toyosawa et al, '98;Kawasaki et al, 2004;Sire et al, 2006). Moreover, the expression of mouse CK14, a mouse-specific epithelial marker, was also detected in those epithelium-derived tissues.…”
Section: Heterospecific Recombinant Teeth Show a Single Cusp Patternmentioning
confidence: 90%